PUSAT KECANTIKAN DI MUARA TEWEH PROVINSI KALIMANTAN TENGAH DENGAN KONSEP NATURAL - Setiarini, Amalia; Wastuty, Prima w (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
Women tend to have a higher potential for stress than men. Continuous stress can lead to physical and psychological problems. One way women release stress is to do activities that make themselves beautiful. This has increased women's interest in beauty, such as in Muara Teweh City. There are various types of beauty facilities available there, but they are not yet integrated in one place. To meet the needs of these women, a Beauty Center is needed that provides various service facilities and goods to facilitate beauty services in one location. The natural concept (space design with a natural atmosphere) is used as a solution in the design because the natural atmosphere is able to absorb negative human energy and release positive energy which has a good psychological impact. The natural atmosphere is presented with the use of natural materials and natural impressions, applied to the elements of space, both inside and outside space.